(3eHGOF GdbGfhf GdJLGQj (B/s - (3GdTQja , YdjGfs; (3GdHGTG, eMeO s; (3GdMdHj, QjGV s ((3YeGf(B: s (3OGQ GdeSjQI(B, s, 2000)
(3eaghe h eUGOQ GdbGfhf GdJLGQj h GdJWQb Gdi GdGYeGd GdJLGQjI h GdJGLQ h GdeJLQ h GdYbhO GdJLGQjI ceG Je JfGhd GdTQcGJ h TQcI GdJVGef h TQcI GdJhUjI GdHSjWI h TQcI GdeMGUI h GdTQcGJ PGJ GdeSDhdjI GdeMOhOI h TQcI GdJhUjI HGdCSge h GdTQcI GdeSGgeI GdYGeI h GNjQG GdGhQGb GdJLGQjI h GdYedjGJ GdeUQajI(B.s
(3edGMb U(B.210 (3eQGLY U(B.251s
Keywords: (3GdbGfhf GdJLGQjs